Bali, masterpiece of the gods - Birch, Miriam; National Geographic Society (U.S.); WQED (Television station : Pittsburgh, Pa.) (Washington, D.C. : National Geographic Society, 1990)
A visit to the island of Bali, focusing on the people, and showing their occupations, religious beliefs and rites, educational system, art, music, dancing, etc.
Subtitles in Indonesian
Title from title screen
Photographed by Mark Knobil ; edited by Barry Nye ; narrated by Richard Kiley ; music, Jay Chattaway
Keywords: Balinese (Indonesian people).; Bali Island (Indonesia) -- Civilization